The Impact of Dating Apps on Hook-up Culture Among Youth in Jaipur - ., Dinky; Dalal, Dr. Payal; Sakshi, Dr.; Amandeep, Pandit; Sharma, Komal (South Eastern European Journal of Public Health, 2024)
This paper is an analysis based on survey findings conducted among Jaipur's GenZ population to understand the prevalence of dating apps and hookup culture among the youth. To my surprise, interest was relatively low for such activities. A large proportion of respondents had never used these trends. Of those who did, most used the hook up apps to connect and make friends rather than for dating. The study examines how Indian youths are still far from embracing Western trends such as hookups and casual relationships in the modern context. Nevertheless, there is a visible shift in their outlook, with most experimenting and finding out what best fits their values and preferences.